2006
DOI: 10.1530/eje.1.02223
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of using recombinant human TSH prior to radioiodine ablation for thyroid cancer, compared with treating patients in a hypothyroid state: the German perspective

Abstract: Objective: This investigation evaluated the cost-effectiveness of radioiodine remnant ablation following preparation with recombinant human TSH (rhTSH), compared with the standard preparation, whereby patients are rendered hypothyroid. Design: The economic evaluation relates to patients with well differentiated thyroid cancer who have undergone thyroidectomy, but have no metastases. The evaluation takes a societal perspective, considering costs and benefits to all parties. The benefits were expressed in units … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 24 publications
(24 reference statements)
2
45
0
2
Order By: Relevance
“…One of the major drawbacks for its more generalized use is its cost (16). Although it is believed that it can be counterbalanced by improved productivity and reduced work absenteeism when hypothyroidism is avoided (17,18), its exact economic impact is difficult to ascertain (19). Our primary goal was to evaluate the whole-body retention time of 131 I, extrapolated from the measurements of the effective dose at a 1-m distance, associated with each strategy of preparing patients for postoperative remnant ablation with 131 I.…”
Section: Discussionmentioning
confidence: 99%
“…One of the major drawbacks for its more generalized use is its cost (16). Although it is believed that it can be counterbalanced by improved productivity and reduced work absenteeism when hypothyroidism is avoided (17,18), its exact economic impact is difficult to ascertain (19). Our primary goal was to evaluate the whole-body retention time of 131 I, extrapolated from the measurements of the effective dose at a 1-m distance, associated with each strategy of preparing patients for postoperative remnant ablation with 131 I.…”
Section: Discussionmentioning
confidence: 99%
“…Під час використання рлТТГ, підвищення рів-ня ТТГ, необхідного для лікувальних та діагностич-них процедур, досягається на тлі замісної терапії тироксином [10][11][12][13][14]. Екзогенна стимуляція рівня ТТГ, завдяки нетривало існуючому гіпотиреозу, дозволяє уникнути майже всіх клінічних симптомів.…”
Section: обґрунтування дослідженняunclassified
“…Mernagh et al 23 conducted a cost-effectiveness evaluation of rhtsh compared with hormone withdrawal and reported that the benefits of rhtsh are achieved with a small incremental societal cost of €47. That difference equates to an incremental costeffectiveness ratio of €950 per quality-adjusted life year, which is considered to be very good value for money, considering that new health care interventions are deemed cost-effective if their incremental costeffectiveness ratio falls below €45,000 23 .…”
Section: Cost Effectivenessmentioning
confidence: 99%
“…That difference equates to an incremental costeffectiveness ratio of €950 per quality-adjusted life year, which is considered to be very good value for money, considering that new health care interventions are deemed cost-effective if their incremental costeffectiveness ratio falls below €45,000 23 .…”
Section: Cost Effectivenessmentioning
confidence: 99%